Traduire pour le Centre national du livre - Hélène Buzelin (Contextes)
Since the mid-eighties, the Centre national du livre in Paris has developed a translation grant programme aimed at encouraging the translation into French of scientific or literary works of high quality. Almost unique in kind, this initiative has kept on supporting around 330 translation projects every year, 60 % of which are submitted to the Commission littératures étrangères. Far from systematic, the grants are allocated following an evaluation of the quality of both the original and its French translation. Following a Descriptive paradigm and based on a fieldwork within the Commission, the present article analyses this evaluation process in order to highlight its underlying dynamics and tensions. In doing so, the author questions what the notions of “ high literary representativeness” and “translation quality” refer to in this translating institution.